Direct Modulation of Heterotrimeric G Protein-coupled Signaling by a Receptor Kinase Complex - Tunc-Ozdemir, Meral (J Biol Chem, 2016)
Plants and some protists have heterotrimeric G protein complexes that activate spontaneously without canonical G protein-coupled receptors (GPCRs). In Arabidopsis, the sole 7-transmembrane regulator of G protein signaling 1 (AtRGS1) modulates the G protein complex by keeping it in the resting state (GDP-bound). However, it remains unknown how a myriad of biological responses is achieved with a single G protein modulator. We propose that in complete contrast to G protein activation in animals, plant leucine-rich repeat receptor-like kinases (LRR RLKs), not GPCRs, provide this discrimination through phosphorylation of AtRGS1 in a ligand-dependent manner. G protein signaling is directly activated by the pathogen-associated molecular pattern flagellin peptide 22 through its LRR RLK, FLS2, and co-receptor BAK1.